Inscribed Athenian laws and decrees 352/1-322/1 BC : epigraphical essays - Lambert, S. D., 1960- (Brill Studies in Greek and Roman Epigraphy, 2012)
This book collects eighteen papers which make original contributions to the study of the inscribed laws and decrees of the city of Athens, 352/1-322/1 BC, the most richly documented period of the city's history. Originally published in academic journals, conference proceedings and Festschriften between 2000 and 2010, they lay groundwork for the author's new edition of these inscriptions, IG II³ Part 1, fascicule 2. The papers, which are based on fresh comprehensive autopsy of the stones and study of squeezes, photographs and early transcripts, report important epigraphical findings (e.g. new readings, restorations, joins and datings), and include studies of onomastics and of the chronology and the history of the period.